PENGARUH METODE FEEDBACK (TIMBAL BALIK) TERHADAP HASIL BELAJAR MATA PELAJARAN FIQIH SISWA KELAS III DI MADRASAH IBTIDAIYAH MUHAMMADIYAH 5 BANYUTENGAHPANCENG GRESIK TAHUN PELAJARAN 2023/2024 - Armitha Damayanti; Maftuhah (STIT Muhammadiyah Paciran, 2023)
The aim of this research is : to determine the implementation of teaching and learning activities using the Feedback (Reciprocity) method and also to find out whether there is an influence of the Feedback (Reciprocity) method on learning outcomes in class III Fiqh subjects at Madrasah Ibtidaiyah Muhammadiyah 5 Banyutengah Panceng Gresik. The feedback methos in student learning outcomes because educators will provide responses to student that can motovate them, give them reinforcement that will make them more confident, make them braver to say what they think, and creating a learning environment that encourages students to participate in discussions. The conclusion of this research is that there is an influence of the Feedback (reciprocity) method in improving student learning outcomes in class III fiqh subjects at Madrasah Ibtidaiyah Muhammadiyah 5 Banyutengah Panceng Gresik as proven by anlysis of pre-test and post-test data using the product moment correlation test with levels significance 0.05 or 5% rcount 0.685 with rtable value 0.4044. Thus, rcount is greater than rtable (0.685 is between 0.60 – 0.799) so it is included in the strong category. Thus, it can be confirmed that learning using the Feedback (Reciprocity) method can improve the quality of student learning outcomes in class III Fiqh subjects at Madrasah Ibtidaiyah Muhammadiyah Banyutengah Panceng Gresik.